Answer:
<h2>(2x - 3y)(4x - y) = 8x² - 14xy + 3y²</h2>
Step-by-step explanation:
Use FOIL: <em>(a + b)(c + d) = ac + ad + bc + bd</em>
(2x - 3y)(4x - y) = (2x)(4x) + (2x)(-y) + (-3y)(4x) + (-3y)(-y)
= 8x² - 2xy - 12xy + 3y²
<em>combine like terms</em>
= 8x² + (-2xy - 12xy) + 3y² = 8x² - 14xy + 3y²
Answer: 12
Step-by-step explanation:
If the first function is
.. h(x) = 2^x
it will be the one that grows the fastest. The exponential function with the largest base value will grow faster than any polynomial.
Answer:
To use a paired t-test
Step-by-step explanation:
t-tests are essentially tests carried out to compare two different groups to check if there is a major difference in their performances or results which may be related in certain characteristics.
A paired (correlated) t-test is used when there are matched pair of similar units or instances of repeated measurements.
In this case, Mary has to use a paired t-test because the samples (students) have high similarity in characteristics. The students in question has to be from the same class to test her hypothesis (similar characteristics).
The function has a horizontal asymptote at y = 1
<h3>How to determine the
horizontal asymptote?</h3>
The function is given as:
f(x) = -4/x + 1
Set the radicand to 0.
So, we have:
y = 0 + 1
Evaluate
y = 1
Hence, the function has a horizontal asymptote at y = 1
Read more about horizontal asymptote at:
brainly.com/question/4084552
#SPJ1